Restructuring: types, causes, and myths about outcomes - Cascio, Wayne F. (Henry Stewart Talks, 2014)
Employment downsizing, Downsizing isn't organizational decline, Downsizing: a form of restructuring, Forms of downsizing, Extent of downsizing, Proactive downsizing, Causes of employment downsizing, Myths about downsizing, The costs of layoffs